LOW AUDIT QUALITY: CLIENT COMPLEXITY AS MODERATING VARIABLE, PRE- AND AT THE PANDEMIC COVID-19 PERIOD - Herusetya, Antonius; Halim, Yiska Cornelia (Universitas Pelita Harapan, 2022)
We suspect that in the era of the COVID-19 pandemic, where physical distance is required by rule, audit quality will decline, especially for small audit firms. This study examines the low audit quality of the modified audit opinion. Low audit quality is measured by low audit tenure and non-Big Four accounting firms. This study also examines this relationship in the era of the COVID-19 pandemic. The sample is all non-financial companies listed on the Indonesia Stock Exchange for 2018-2020. Using logistic regression analysis in our models, our study show contrary empirical evidence to our hypothesis that low audit tenure and non-Big Four audit firms are positively related to modified audit opinion. However, this study found no evidence that client complexity affects the relationship between low audit tenure and non-big four with modified audit opinions, both in the entire observation period and during the COVID-19 era. Our results give new implications to the stakeholders that audit quality of low tenure and non-Big Four firms do not automatically decline in the era of the COVID-19 pandemic.